A Note on Implicit and Explicit Mann Iterative Processes for Asymptotically 𝜙-Strongly Pseudocontractive Mappings - Luigi Muglia; Yonghong Yao (Journal of Applied Mathematics)
In this paper we prove the equivalence and the strong convergence of an explicit Mann iterative process and a modified implicit iterative process for asymptotically 𝜙-strongly pseudocontractive mappings in a uniformly smooth Banach space.